Miocene marine-continental correlations in the Lisbon area and some discussion related to personnal experience - Antunes, M. Telles (2010)
Sandpit exploitation near Lisbon allowed collecting of many Miocene, non marine fossils. These sands are part of the mostly marine Miocene series in the Lower Tagus basin. The particularly favourable situation led several researchers to deal with marine-continental correlations. Difficulties often concern methodologic aspects. Some poorly based interpretations exerced a lasting influence. A critical approach is presented. Analysis requires data. Methods based upon models often lead to the temptation of fitting data in order to confirm a priori conclusions, or of mixing up data as if of equal statistic value while they have not at all the same weight. Erroneous interpretations' uncritical repetition for many years "upgraded" them into absolute truth. Another point is endemism vs. europeism. Miocene mammals from Lisbon compared well with corresponding French, contemporaneous taxa, while this was apparently not true for Spanish ones. Too much accent had been put on the endemic character of Spanish, or even regional, mammalian faunas. Nationalist bias and sensationalism also weigh, albeit negatively. Meanwhile nearly all the more evident examples as the rhinoceros Hispanotherium are discredited as Iberian endemisms. Taxa may appear as endemic just because they have not yet been found elsewhere. At least for the medium to large-sized mammals, with their huge geographic distribution, faunal differences depend much more on ecology, climate and environmental conditions. Emphasis on differences may also result from researchers that are often in a precarious situation and need very much to achieve short-term, preferably sensational results. Overvalued differences may mask real similarities. Unethic and not scientific behaviour are further enhanced by "nomina nuda" tricks that may simply be a way to circunvent or cheat the Priority Rule. On the other hand, access to communication networks may present as sensational novelties items that are not new at all, misleading the audience. A new class of "science people" arose, created by the media and not by the value of their real achievements. Discussion is presented on sedimentation processes and discontinuities that are often regarded as absolute precision dating tools, as well as on some geochemical and paleomagnetic interpretations. A very good chronologie frame has been obtained for the basin under study on the basis of an impressive set of data, providing a rather detailed and accurate frame for Miocene marine-continental correlations.